2018
DOI: 10.1096/fj.201700690r
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of PKC‐ α is associated with cell cycle arrest and erythroid differentiation in myelodysplastic syndromes (MDSs)

Abstract: PI-PLCβ1 is involved in cell proliferation, differentiation, and myelodysplastic syndrome (MDS) pathogenesis. Moreover, the increased activity of PI-PLCβ1 reduces the expression of PKC-α, which, in turn, delays the cell proliferation and is linked to erythropoiesis. Lenalidomide is currently used in low-risk patients with MDS and del(5q), where it can suppress the del(5q) clone and restore normal erythropoiesis. In this study, we analyzed the effect of lenalidomide on 16 patients with low-risk del(5q) MDS, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…MDS are a group of hematological diseases characterized by impairment in cell differentiation and proliferation [79,85]. About 30% of confirmed MDS cases evolve into AML, so it is imperative to identify biomolecular markers associated with the risk of AML evolution in MDS patients [86][87][88].…”
Section: Plcs In Cancer Cell Proliferation Survival and Tumor Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…MDS are a group of hematological diseases characterized by impairment in cell differentiation and proliferation [79,85]. About 30% of confirmed MDS cases evolve into AML, so it is imperative to identify biomolecular markers associated with the risk of AML evolution in MDS patients [86][87][88].…”
Section: Plcs In Cancer Cell Proliferation Survival and Tumor Growthmentioning
confidence: 99%
“…MDS are a group of hematological diseases characterized by impairment in cell differentiation and proliferation [79,85]. About 30% of confirmed MDS cases evolve into AML, so it is imperative to identify biomolecular markers associated with the risk of AML evolution in MDS patients [86][87][88]. Our group showed that monoallelic deletion of PLCβ1 gene in MDS patients showed worse clinical outcomes with an increased probability of evolving into AML On the other hand, upstream activators of PLCγ, like EGF and PDGF are major regulators of cell growth and proliferation [93].…”
Section: Plcs In Cancer Cell Proliferation Survival and Tumor Growthmentioning
confidence: 99%
“…In these cells, a nuclear translocation of PKC-, associated with erythropoiesis, was also detected. These results better explain the role of PI-PLC1/PKC- signaling in erythropoiesis and lead to a better comprehension of the lenalidomide effect on del(5q) MDS, opening the way to innovative, targeted therapies (45). These mechanisms underline the potential of nuclear PI-PLC1 to become a prognosis stratification marker and a treatment-predictive outcome marker in patients with MDS.…”
Section: Hematological Disordersmentioning
confidence: 67%
“…More recently, a study on the effect of lenalidomide on 16 patients with lower-risk MDS and deletion of the long arm of chromosome 5 [del(5q)], as well as del(5q) and nondel(5q) hematopoietic cell lines, focused on erythropoiesis, cell cycle, and PI-PLC1/protein kinase C- (PKC-) signaling (45). Indeed, nuclear PI-PLC1 is a negative regulator of erythroid differentiation (46), and it specifically targets PKC-, which, in turn, has been associated with proliferation and differentiation of human erythroleukemia cells (47).…”
Section: Hematological Disordersmentioning
confidence: 99%
“…Little is known about the molecular effect of lenalidomide, but, currently, the best hypothesis is that it suppresses the del(5q) clone and restores a normal erythropoiesis [20,92,93]. One study analyzed the effect of lenalidomide on 16 patients with low-risk del(5q) MDS, as well as del(5q) and non-del(5q) hematopoietic cell lines, focusing on erythropoiesis, cell cycle, and PLCβ1/PKCα signaling [94]. This study revealed PLCβ1 localization within the cytoplasm of the del(5q) cells, whereas, in the same subpopulation, PKCα, a serine/threonine kinase downstream of PLCβ1, translocated to the nucleus.…”
Section: Plcβ1mentioning
confidence: 99%